A multifunctional chemical linker in a buried interface for stable and efficient planar perovskite solar cells. Issue 36 (7th September 2022) - Geng, Quanming; Xu, Zong; Song, Wenwu; Hu, Yanqiang; Sun, Guangping; Wang, Jin; Wang, Minmin; Sun, Tongming; Tang, Yanfeng; Zhang, Shufang
Abstract : A variable structure broad-spectrum UV absorber is employed as a multifunctional chemical linker for a buried interface to improve the photovoltaic performance of planar perovskite solar cells. Abstract : The buried interface between a perovskite (PVK) light absorbing layer and an electron transport layer (ETL) plays an utmost important role in further improving the efficiency and stability of planar perovskite solar cells (PSCs). The interfacial properties greatly affect charge transport, perovskite crystal growth, and device stability. Herein, a variable structure broad-spectrum UV-284 absorber agent 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (HMBS) is introduced into PSCs based on SnO2 ETLs as an efficient multifunctional chemical linker to modify the buried interface properties. HMBS used to modify SnO2 can simultaneously suppress the surface trap states of ETLs, optimize the ETL/PVK interface energy level arrangement, and improve the crystallization quality of the upper perovskite films. Meanwhile, as an efficient UV absorber, HMBS can also greatly reduce the damage caused by UV light to perovskite films and thus improve the stability of devices. Consequently, HMBS-modified PSCs exhibit champion efficiencies of 23.42% (0.09 cm 2 ) and 20.63% (1.00 cm 2 ) along with remarkably enhanced UV stability. This work emphasizes the importance of appropriate interface treatment strategies for buried interface modification and provides an effective method for fabricating efficient and UV resistant perovskite photovoltaic devices.